Genre specificity of vandal graphic damage to urban spaces - Babikova, Marina Rashitovna; Kruzhkova, Olga Vladimirovna (Жанры речи)
The visual space of a modern city and any other populated area is very diverse and rich, both with useful elements: signs, road signs, posters, street names, etc., and with the elements which change the appearance of streets in a negative way, namely the graphic damage to urban space or unauthorized graffiti, which is in the focus of this paper. The relevance of the present study is determined by the significance of studying various types of everyday written and speech activities within the city space. The specificity of graffiti as an object of linguistic research is noteworthy. Being an ambiguous part of urban space, graphic damage is often not fully studied, but nevertheless has significant pragmatic potential that can influence the opinion of citizens. Thus, the purpose of the study is to describe graphic damage, considering the entire range of extralinguistic and linguistic components of the genre. The work is based on a descriptive research method, and the basis for the methodology for describing the genre is the model of a complex communicative-typological description of the natural written Russian speech, proposed by N. B. Lebedeva and adapted to the objectives of this study. Thus, the article presents a description of aspects of the genre under consideration through a number of characteristics: 1) author, 2) purpose, 3) addressee, 4) content, 5) communicative time, 6) linguistic embodiment, 7) social assessment 8) cognitive dominant of the genre.